THE CONTRIBUTION AND ROLE OF LANGUAGE CENTERS IN ACTUALIZING WORLD-CLASS UNIVERSITY - M. Abdul Hamid; Siti Fatimah; M. Abdullah Charis (Lentera Pendidikan: Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aimed to investigate the contribution and role of Language Centers in actualizing World-Class University within the State Islamic Higher Education (PTKIN). This research was a case study using qualitative approach. The subjects were two Language Centers located at UIN Syarif Hidayatullah Jakarta and UIN Maulana Malik Ibrahim Malang. In collecting data, researchers conducted interviews and documentation. The data collected were analyzed through data reduction, presentation, and conclusion. The results showed that the contribution and role of the Language Centers were very significant in supporting the actualization of World-Class University. Both Language Centers have contributed to a) improve/increase foreign language skills, b) detect language skills, c) archive important translated documents, and d) organizing language-related training or workshops. They had a role in building a global university brand through international cooperation, seminars or conferences, and sending lecturers to Al-Azhar University in Egypt to introduce the Indonesian language and culture.